PENINGKATAN HASIL BELAJAR IPS DENGAN COOPERATIVE LEARNING TIPE GROUP INVESTIGATION DI SDN KOTA BUKITTINGGI - Sari, Riri Permata (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Condition of study of elementary school specially social science at the moment still using many model learn conventionally, student only becoming teacher and object only expecting student sit to be kept quiet, hear and note without asking for student find by self existing problems. As a result lackluster student oftentimes and feel saturated in study so that result of learning of lowering. To increase result and activity learn student in study of IPS  conducted by research of class action by using model Cooperative Learning Tipe Group Investigation. From the research, the second cycle of cognitive learning outcomes with an average grade of 85.1, the number of students who complete 26 students and 3 students who have not completed the percentage of students passing grade is 89.6%. student learning outcomes of affective aspects with an average grade 85.8, the number of students who pass is 26 and who have not completed 3 students, with a percentage of 89.6% mastery learning students, and student learning outcomes of psychomotor aspect with an average grade 85, the number of students who pass are 26 students and 3 students who have not completed the percentage of students passing grade is 89.6%.  Kata Kunci: Ilmu PengetahuanSosial; Hasil Belajar; Cooperative Learning Tipe Group Investigation